O enclave de cabinda no contexto do anticolonialismo e da independência de Angola 1960-1975 - Marques, Roger Machado (2022)
This work analyzes the nationalist manifestations of the Enclave of Cabinda, among the years of anti-colonial struggles until the independence of the Portuguese colonies in Africa, with a focus on Angola, covering a time frame that goes from 1960 to 1975. The study seeks to understand the position that the Enclave occupied in the geopolitical context of the Cold War and, as the region was articulated according to the political moment of decolonization and independence of Angola. In addition, the research analyzes the factors that led to the formation of Cabindan nationalism and where this awareness originated, among the popular layers understood as “indigenous” or within the intellectual elite of “assimilates”. To observe the problem, authors specialized in the nationalist phenomenon are used, the main theoretical lens used to observe the political discourses of the independence movements in Cabinda. The nerve center of Cabinda identity is the Treaty of Simulambuco, signed during the years of the Berlin Conference on February 1, 1885. Throughout the political history of the Enclave of Cabinda, the historic treaty has been instrumentalized in line with the main regional political developments. As a conclusion of this work, the most significant historical moments where the Treaty of Simulambuco is mobilized will be discussed, and what would be the political uses of the regional history of Cabinda.